First-principles study of elastic and thermal properties of scheelite-type molybdates and tungstates. (September 2020) - Najafvandzadeh, N.; López-Moreno, S.; Errandonea, D.; Pavone, P.; Draxl, C.
Abstract: First-principles calculations are carried out to study the physical properties of scheelite-type A MoO4 molybdates and A WO4 tungstates ( A = Ca, Sr, Ba, and Pb). We consider two flavors for the exchange-correlation functional, the local-density approximation (LDA) and the generalized gradient approximation (GGA). The second-order elastic constants were determined, and we found that c 11 is larger than c 33 for the eight investigated compounds. This fact is consistent with the well-known anisotropic compressibility of scheelite-type molybdates and tungstates. The calculated elastic constants are used to determine macroscopic properties which are relevant for applications, such as the bulk, shear, and Young modulus, as well as the Poisson ratio, and Vickers hardness. Other physical properties like sound wave velocities, Debye temperature, and thermal conductivity are also calculated. All these properties are relevant for many of the technological applications of scheelite-type tungstates and molybdates. The obtained results are in good agreement with previous calculations and experimental data when available and provide a systematic understanding of properties of scheelite-type oxides.